2017
DOI: 10.1016/j.redox.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Altered bioenergetics and enhanced resistance to oxidative stress in human retinal pigment epithelial cells from donors with age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness among older adults. It has been suggested that mitochondrial defects in the retinal pigment epithelium (RPE) underlies AMD pathology. To test this idea, we developed primary cultures of RPE to ask whether RPE from donors with AMD differ in their metabolic profile compared with healthy age-matched donors. Analysis of gene expression, protein content, and RPE function showed that these cultured cells replicated many of the cardinal features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
139
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 48 publications
17
139
1
Order By: Relevance
“…The effects on energy/metabolic pathways led us to analyze mitochondrial function. Consistent with previous reports, we found a decrease in metabolic capacity . All four parameters (mitochondrial basal respiration, ATP production, maximal respiration, and spare respiratory capacity) were significantly lower in cell lines from individuals with AMD compared to normal controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The effects on energy/metabolic pathways led us to analyze mitochondrial function. Consistent with previous reports, we found a decrease in metabolic capacity . All four parameters (mitochondrial basal respiration, ATP production, maximal respiration, and spare respiratory capacity) were significantly lower in cell lines from individuals with AMD compared to normal controls.…”
Section: Discussionsupporting
confidence: 92%
“…Our microarray array data showed altered gene expression in metabolic‐related pathways (Table ). Furthermore, earlier studies of bioenergetics demonstrate mitochondrial dysfunction in RPE cells from patients with AMD . Therefore, we analyzed mitochondrial function of iPSC‐derived RPE cells using the Seahorse platform .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, energy metabolism of primary RPE cells isolated from AMD patients was found to be strongly impaired compared to RPE cells from healthy controls [9]. In this model, glycolysis as well as mitochondrial respiration were reduced in RPE cells from AMD patients [9]. Other studies showed that mitochondrial dysfunction in RPE cells may represent a relevant AMD feature.…”
Section: Introductionmentioning
confidence: 97%
“…Ageing processes in combination with external stressors, such as smoking or a high fat diet [7, 8], force RPE cells to deal with excessive levels of oxidative stress. In fact, energy metabolism of primary RPE cells isolated from AMD patients was found to be strongly impaired compared to RPE cells from healthy controls [9]. In this model, glycolysis as well as mitochondrial respiration were reduced in RPE cells from AMD patients [9].…”
Section: Introductionmentioning
confidence: 99%